Constrained Weak Nash-Type Equilibrium Problems - W. C. Shuai; K. L. Xiang; W. Y. Zhang (Abstract and Applied Analysis)
A constrained weak Nash-type equilibrium problem with multivalued payoff functions is introduced. By virtue of a nonlinear scalarization function, some existence results are established. The results extend the corresponding one of Fu (2003). In particular, if the payoff functions are singlevalued, our existence theorem extends the main results of Fu (2003) by relaxing the assumption of convexity.